Probing the Relationship Between Early Star Formation and CO in the Dwarf Irregular Galaxy WLM with JWST - Archer, Haylee N.; Hunter, Deidre A.; Elmegreen, Bruce G.; Rubio, Monica; Cigan, Phil; Windhorst, Rogier A.; Cortés, Juan R.; Jansen, Rolf A. (The Astronomical journal, 2024)
Wolf–Lundmark–Melotte (WLM) is a Local Group dwarf irregular (dIrr) galaxy with a metallicity 13% of solar. At 1 Mpc, the relative isolation of WLM provides a unique opportunity to investigate the internal mechanisms of star formation at low metallicities. The earliest stages of star formation in larger spirals occur in embedded clusters within molecular clouds, but dIrrs lack the dust, heavy metals, and organized structure of spirals believed necessary to collapse the molecular clouds into stars. Despite actively forming stars, the early stages of star formation in dIrrs is not well understood. We examine the relationship between early star formation and molecular clouds at low metallicities. We utilize ALMA-detected CO cores, JWST near-infrared (NIR) images (F090W, F150W, F250M, and F430M), and GALEX far-ultraviolet (FUV) images of WLM to trace molecular clouds, early star formation, and longer star formation timescales respectively. We compare clumps of NIR-bright sources (referred to as objects) categorized into three types based on their proximity to FUV sources and CO cores. We find objects, independent of their location, have similar colors and magnitudes and no discernible difference in temperature. However, we find that objects near CO have higher masses than objects away from CO, independent of proximity to FUV. Additionally, objects near CO are coincident with Spitzer 8 μ m sources at a higher frequency than objects elsewhere in WLM. This suggests objects near CO may be embedded star clusters at an earlier stage of star formation, but accurate age estimates for all objects are required for confirmation.